A Psychometric Study of the Bayley Scales of Infant and Toddler Development in Persian Language Children - AZARI, Nadia; SOLEIMANI, Farin; VAMEGHI, Roshanak; SAJEDI, Firouzeh; SHAHSHAHANI, Soheila; KARIMI, Hossein; KRASKIAN, Adis; SHAHROHI, Amin; TEYMOURI, Robab; GHARIB, Masoud (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Azari. N, Soleimani F, Vameghi R, Sajedi F, Shahshahani S, Karimi H, Kraskian A, Shahrokhi A, Teymouri R, Gharib M. A Psychometric Study of the Bayley Scales of Infant and Toddler Development in Persian Language Children. Iran J Child Neurol. Winter 2017; 11(1):50-56. Abstract Objective Bayley Scales of infant & toddler development is a well-known diagnostic developmental assessment tool for children aged 1–42 months. Our aim was investigating the validity & reliability of this scale in Persian speaking children. Materials & Methods The method was descriptive-analytic. Translation- back translation and cultural adaptation was done. Content & face validity of translated scale was determined by experts’ opinions. Overall, 403 children aged 1 to 42 months were recruited from health centers of Tehran, Iran during years of 2013- 2014 for developmental assessment in cognitive, communicative (receptive & expressive) and motor (fine & gross) domains. Reliability of scale was calculated through three methods; internal consistency using Cronbach’s alpha coefficient, test-retest and interrater methods. Construct validity was calculated using factor analysis and comparison of the mean scores methods. Results Cultural and linguistic changes were made in items of all domains especially on communication subscale. Content and face validity of the test were approved by experts’ opinions. Cronbach’s alpha coefficient was above 0.74 in all domains. Pearson correlation coefficient in various domains, were ≥ 0.982 in test retest method, and ≥0.993 in inter-rater method. Construct validity of the test was approved by factor analysis. Moreover, the mean scores for the different age groups were compared and statistically significant differences were observed between mean scores of different age groups, that confirms validity of the test. Conclusion The Bayley Scales of Infant and Toddler Development is a valid and reliable tool for child developmental assessment in Persian language children. References 1. Boyle CA, Boulet S, Schieve LA, Cohen RA, Blumberg SJ, Yeargin-Allsopp M, et al. Trends in the prevalence of developmental disabilities in US children, 1997–2008. Pediatrics 2011:peds. 2010-989. 2. Sajedi F, Doulabi MA, Vameghi R, Baghban AA, Mazaheri MA, Mahmodi Z, et al. Development of Children in Iran: A Systematic Review and Meta-Analysis. Glob J Health Sci 2015 Dec 18;8(8):51251. 3. Soleimani F, Vameghi R, Biglarian A, Rahgozar M. Prevalence of motor developmental disorders in children in Alborz Province, Iran in 2010. Iran Red Crescent Med J 2014 Dec 25;16(12):e16711. 4. Soleimani F, Vameghi R, Biglarian A. Antenatal and Intrapartum Risk Factors for Cerebral Palsy in Term and Near-term Newborns. Arch Iran Med 2013;16(4): 213 – 216. 5. Soleimani F, Vameghi R, Biglarian A, Daneshmandan N : Risk factors Associated with Cerebral Palsy in Children Born in Eastern and Northern Districts of Tehran. Iran Red Crescent Med J 2010; 12 (4):428-432. 6. Fischer VJ, Morris J, Martines J. Developmental Screening Tools: Feasibility of Use at Primary Healthcare Level in Low-and Middle-income Settings. J Health Popul Nutr 2014 Jun;32(2):314-26. 7. Blauw-Hospers CH, Hadders-Algra M. A systematic review of the effects of early intervention on motor development. Dev Med Child Neurol 2005 Jun;47(6):421-32. 8. Nordhov SM, Ronning JA, Dahl LB, Ulvund SE, Tunby J, Kaaresen PI. Early intervention improves cognitive outcomes for preterm infants: randomized controlled trial. Pediatrics 2010 Nov;126(5):e1088-94. 9. Bailey DB, Jr., Hebbeler K, Scarborough A, Spiker D, Mallik S. First experiences with early intervention: a national perspective. Pediatrics 2004 Apr;113(4):887-96. 10. Raju TN, Higgins RD, Stark AR, Leveno KJ. Optimizing care and outcome for late-preterm (near-term) infants: a summary of the workshop sponsored by the National Institute of Child Health and Human Development. Pediatrics 2006;118(3):1207-14. 11. First LR, Palfrey JS. The infant or young child with developmental delay. N Engl J Med 1994 Feb 17;330(7):478-83. 12. Dobrez D, Sasso AL, Holl J, Shalowitz M, Leon S, Budetti P. Estimating the cost of developmental and behavioral screening of preschool children in general pediatric practice. Pediatric 2001;108(4):913-22. 13. Torras-Mana M, Guillamon-Valenzuela M, Ramirez-Mallafre A, Brun-Gasca C, Fornieles-Deu A. Usefulness of the Bayley scales of infant and toddler development, third edition, in the early diagnosis of language disorder. Psicothema 2014;26(3):349-56. 14. Gladstone M, Lancaster GA, Jones A, Maleta K, Mtitimila E, Ashorn P, et al. Can Western developmental screening tools be modified for use in a rural Malawian setting? Arch Dis Child. 2008 Jan;93(1):23-9. 15. Lipkin PH, Cartwright JD, Desch LW, Duby JC, Elias ER, Johnson CP, et al. Role of the medical home in family-centered early intervention services. Pediatrics 2007;120(5):1153-8. 16. Johnson S, Marlow N. Developmental screen or developmental testing? Early Hum Dev 2006 Mar;82(3):173-83. 17. Vameghi R, Sajedi F, Kraskian Mojembari A, Habiollahi A, Lornezhad HR, Delavar B. Cross-Cultural Adaptation, Validation and Standardization of Ages and Stages Questionnaire (ASQ) in Iranian Children. Iran J Public Health 2013 May 1;42(5):522-8. 18. Shahshahani S, Vameghi R, Azari N, Sajedi F, Kazemnejad A. Validity and Reliability Determination of Denver Developmental Screening Test-II in 0-6 Year-Olds in Tehran. Iran J Pediatr 2010 Sep;20(3):313-22. 19. Abubakar A, Holding P, Van Baar A, Newton C, van de Vijver FJ. Monitoring psychomotor development in a resourcelimited setting: an evaluation of the Kilifi Developmental Inventory. Ann Trop Paediatr 2008 Sep;28(3):217-26. 20. Harris SR, Megens AM, Backman CL, Hayes VE. Stability of the Bayley II Scales of Infant Development in a sample of low-risk and high-risk infants. Dev Med Child Neurol 2005 Dec;47(12):820-3. 21. Albers CA, Grieve AJ. Review of Bayley Scales of Infant and Toddler Development. J Psychoeduc Assess 2007 Jun;25(2):180-190. DOI: 10.1177/0734282906297199. 22. Godamunne P, Liyanage C, Wimaladharmasooriya N, Pathmeswaran A, Wickremasinghe AR, Patterson C, et al. Comparison of performance of Sri Lankan and US children on cognitive and motor scales of the Bayley scales of infant development. BMC Res Notes 2014 May 16;7:300. 23. Deroma L, Bin M, Tognin V, Rosolen V, Valent F, Barbone F, et al. [Interrater reliability of the Bayley III test in the Italian Northern-Adriatic Cohort II]. Epidemiol Prev 2013 Jul-Oct;37(4-5):297-302. 24. Zakaria S, Seok CB, Sombuling A, Ahmad MS, Hashmi SI. Reliability and Validity for Malay Version of Bayley Scales of Infant and Toddler Development-(Bayley- III): Preliminary Study. International Proceedings of Economics Development & Research 2012;40. 25. Yu YT, Hsieh WS, Hsu CH, Chen LC, Lee WT, Chiu NC, et al. A psychometric study of the Bayley Scales of Infant and Toddler Development - 3rd Edition for term and preterm Taiwanese infants. Res Dev Disabil 2013 Nov;34(11):3875-83. 26. Acton BV, Biggs WS, Creighton DE, Penner KA, Switzer HN, Thomas JHP, et al. Overestimating neurodevelopment using the Bayley-III after early complex cardiac surgery. Pediatrics 2011 Oct;128(4):e794-800. 27. Anderson PJ, De Luca CR, Hutchinson E, Roberts G, Doyle LW. Underestimation of developmental delay by the new Bayley-III Scale. Arch Pediatr Adolesc Med 2010 Apr;164(4):352-6. 28. Campbell SK, Zawacki L, Rankin KM, Yoder JC, Shapiro N, Li Z, et al. Concurrent validity of the TIMP and the Bayley III scales at 6 weeks corrected age. Pediatr Phys Ther 2013 Winter;25(4):395-401. 29. Visser L, Ruiter SAJ, Van der Meulen BF, Ruijssenaars WAJJM, Timmerman ME. Validity and suitability of the Bayley-III Low Motor/Vision version: A comparative study among young children with and without motor and/or visual impairments. Res Dev Disabil 2013 Nov;34(11):3736-45. 30. Soleimani F, Azari N, Vameghi R, Sajedi F, Shahshahani S, Karimi H, Kraskian A, Shahrokhi A, Teymouri R, Gharib M. Is the Bayley Scales of Infant and Toddler Developmental Screening Test, valid and reliable for Persian speaking children? Iran J Pediatr 2016 October; 26(5):83-90.